PENGARUH NILAI TUKAR RUPIAH, TINGKAT SUKU BUNGA SBI, INFLASI DAN HARGA MINYAK MENTAH TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK JAKARTA - ME, GETY HENDRIKA (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This researchtries to explainhow is thecorrelation fromseveral independent variableswiththe dependent variables, whichis statedinto ahypothesis: 1)inflation(variable X1) hasa positivecorrelationto thestock price index(variable Y),2)interest rate(variable X2) has apositivecorrelationto thestock price index(variable Y), 3)U.S. dollar exchange(variable X3) hasa negativecorrelationto stock price index(variable Y), 4)crude oil price (variable X4) has a positive correlation to the stock price index (variable Y), 5) inflation, interest rates, U.S. dollar exchange and crude oil prices is affect the stock price index. The method usedisMultiple Regression, complemented by classic assumption test. Data obtained from the Monthly Statictic, Indonesia Stock Exchange, Economic Indicators of the National Bureau of Statistic and Monthly Report of Bank Indonesia (SEKI). Sampling using purposive sampling and data collected by noting the time series, and then processing using Eviews program. The resultsof this calculationsis based oncalculation of data SBI and U.S. Dollar Exchange, either individual or together, significantly affect the stock price index at the Jakarta Stock, during the period of the study, the year of 2007 2011, and inflation data and oil price raw, either individually or together, did not significantly affect the stock price index at Jakarta Stock Exchange during the periode of study 2007 2011 and also was the conclusion of this thesis. Interms of the rate of inflation to be positively correlated with the stock price index, the SBI rate is negatively correlated with the stock price index, the U.S. Dollar Exchange rate is negative correlated with the stock price index and the price of crude oil is positively correlated with the stock price index. As the value ofR-square of 0.546941, meansthe prediction stock price index can be explained by the four independent variable; inflation, interest rates, U.S. Dollar Exchange, and crude oil price amounted 54,69%, while the remaining 45,31% is affected by other causes beyond the model, it is advised to study futher by incorporating additional variables, such as economic growth, the financial posisiton of company, the company dividend policy, and investment policy of the company. Keywords: inflation, interest rate, U.S. Dollar Exchange, and crude oil price, composite stock price index